2020
DOI: 10.3390/biology9080230
|View full text |Cite
|
Sign up to set email alerts
|

Physioxia Expanded Bone Marrow Derived Mesenchymal Stem Cells Have Improved Cartilage Repair in an Early Osteoarthritic Focal Defect Model

Abstract: Focal early osteoarthritis (OA) or degenerative lesions account for 60% of treated cartilage defects each year. The current cell-based regenerative treatments have an increased failure rate for treating degenerative lesions compared to traumatic defects. Mesenchymal stem cells (MSCs) are an alternative cell source for treating early OA defects, due to their greater chondrogenic potential, compared to early OA chondrocytes. Low oxygen tension or physioxia has been shown to enhance MSC chondrogenic matrix conten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Additionally, hypoxic pretreatment can also upregulate genes related to growth, cell signaling, metabolism, and cellular stress response pathways [ 113 ]. In a rabbit knee joint trauma and focal early OA model, hypoxia-pretreated MSC+HA hydrogel caused a significant improvement in the cartilage repair score [ 114 ]. The mechanism through which hypoxia affects cells is mainly regulated by HIF-1.…”
Section: Stem Cell Pretreatment Strategymentioning
confidence: 99%
“…Additionally, hypoxic pretreatment can also upregulate genes related to growth, cell signaling, metabolism, and cellular stress response pathways [ 113 ]. In a rabbit knee joint trauma and focal early OA model, hypoxia-pretreated MSC+HA hydrogel caused a significant improvement in the cartilage repair score [ 114 ]. The mechanism through which hypoxia affects cells is mainly regulated by HIF-1.…”
Section: Stem Cell Pretreatment Strategymentioning
confidence: 99%
“…However, research by Hu et al showed that when cells were cultured at an oxygen concentration lower than 0.5%, hypoxic pretreatment (HP) increased MSC migration and reduced MSC apoptosis [ 71 ]. In terms of OA and cartilage repair, in rabbit knee joint trauma and focal early OA models, aerobic MSC treatment significantly improved cartilage repair scores compared with hyperoxic MSC and their respective control defects [ 72 ]. Rong et al found that EVs derived from BMSCs treated with hypoxia-inducible factor 1α-induced hypoxic can promote chondrocyte proliferation, migration, and inhibit apoptosis through the miR-216a-5p/JAK2/STAT3 signaling pathway as well as mediate cartilage repair in osteoarthritis [ 73 ].…”
Section: Cell Pretreatment Strategymentioning
confidence: 99%
“…The joint focal defect method is an ideal model for observing the early manifestations and treatment effects of OA. It is particularly sensitive in observing the therapeutic effects of cartilage protection and repair [112,113].…”
Section: Induced Models (Surgery or Injection)mentioning
confidence: 99%